2021
DOI: 10.3390/nu13092909
|View full text |Cite
|
Sign up to set email alerts
|

The Health Effects of Chocolate and Cocoa: A Systematic Review

Abstract: Chocolate has a history of human consumption tracing back to 400 AD and is rich in polyphenols such as catechins, anthocyanidins, and pro anthocyanidins. As chocolate and cocoa product consumption, along with interest in them as functional foods, increases worldwide, there is a need to systematically and critically appraise the available clinical evidence on their health effects. A systematic search was conducted on electronic databases such as MEDLINE, EMBASE, and Cochrane Central Register of Controlled Trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 50 publications
0
23
1
Order By: Relevance
“…Beetroot juice is a scientifically proven supplement. It is a popular additive that has been widely studied for its effects on improving the ability to perform long-term submaximal training [ 172 ] and intense, intermittent, short-term exercise [ 132 , 173 ] ( Table 3 ). Its beneficial effect in the context of sports is due to the high content of nitrates (NO 3 − ), compounds found naturally in vegetables.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Beetroot juice is a scientifically proven supplement. It is a popular additive that has been widely studied for its effects on improving the ability to perform long-term submaximal training [ 172 ] and intense, intermittent, short-term exercise [ 132 , 173 ] ( Table 3 ). Its beneficial effect in the context of sports is due to the high content of nitrates (NO 3 − ), compounds found naturally in vegetables.…”
Section: Resultsmentioning
confidence: 99%
“…One study found that dietary nitrates increase performance during repeated sprints and may ameliorate the cognitive decline (particularly in reaction time) that may occur with prolonged repetitive exercise [ 132 ]. In another randomized, double-blind, placebo-controlled, parallel group study, 40 healthy adults received a placebo or 450 mL of beetroot juice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Natural antioxidants inhibiting ROS production are fundamental in protecting the ear from age-induced damage. In this sense, cocoa and its derivates have been shown to contain important antioxidants such as polyphenolic compounds [ 27 ]. This biological property points to cocoa polyphenols as interesting candidates for cellular protection.…”
Section: Discussionmentioning
confidence: 99%